The Use of Urtica dioica (Stinging Nettle) as a Blood Sugar Lowering Herb: A Case Report and a Review of the Literature - Bisrat Hailemeskel; Fekadu Fullas (Diabetes Research, 2015)
Introduction: Medicinal plants have been used in traditional medicine to manage blood sugar levels in patients with diabetes, but only a few of them have received scientific investigation. Many patients tend to self-medicate with herbal supplements, based on information they obtain from various sources. Case Summary: A 57 year-old African-American male with diabetes had been prescribed metformin. He started on his own taking Stinging Nettle concurrently with metformin, which led to hypoglycemia. He then stopped taking metformin and continued with the herb. His morning fasting blood sugar stayed at less than 120 mg/dL. Because of accessibility, several months later he then discontinued taking Stinging Nettle, at which time his blood glucose level climbed up to 140-160 mg/dL. At this point, he saw his healthcare provider who put him back on metformin, and his blood glucose was well managed after that. Conclusion: A systematic literature evaluation on Stinging Nettle showed some evidence of the blood sugar lowering effect of the plant. The patient in this case may have benefited from this property of the plant. Considering poor regulation and the possible variation of herbal supplement products in the market, routine use of Stinging Nettle should not be encouraged. However, there is some evidence on the blood lowering property of Stinging Nettle.